The Application of Morals from an Early Age as a Preventive Effort Against Violent Behavior - Samudra, Shinta Kristantiara; Anwar, Latifah (Universitas Ibn Khaldun, 2025)
This research examines the application of morals as a preventive effort against violent behavior, especially among teenagers. The background of this research rests on the moral dilemma that is increasingly prominent, marked by the increasing cases of violence, bullying, and juvenile delinquency that reflect the degradation of moral values in social life. This study aims to explore the relevance of moral values taught in the hadith of the Prophet Muhammad in shaping harmonious individual character and preventing violent behavior. The method used is qualitative research with a library research approach, referring to classical literature such as kutub al-Sittah and relevant modern books. The results showed that family, friendship, social, and individual emotional environment factors greatly contribute to violent behavior. However, the application of moral values derived from the hadith can be a preventive solution. In a personal context, good morals help individuals control their emotions and respond peacefully to conflict. In the family, morals support the creation of harmonious relationships, while in society, moral values encourage respectful interactions. In conclusion, the implementation of moral teachings in daily life has a significant impact in reducing cases of violence. This research emphasizes the importance of moral education from an early age to build a generation with morals and good character.